Supports and barriers to implementation of routine clinical assessment for children with cerebral palsy: A mixed-methods study. Issue 4 (13th February 2018) - Kerr, Claire; Shields, Nora; Quarmby, Lyndsay; Roberts, Karen; Imms, Christine
Abstract: Purpose: The purpose of this study is to investigate supports and barriers to evidence-based routine clinical assessment of children with cerebral palsy. Method: This mixed methods study included physiotherapists, occupational therapists and speech pathologists providing services to children with cerebral palsy (3–18 years) within five organizations across Australia. Four organizations initiated standardized routine clinical data collection (Commencing organizations), and one had previously mandated routine assessment (Comparison organization). Participants completed the Supports and Barriers Questionnaire ( n  = 227) and participated in focus groups ( n  = 8 groups, 37 participants). Quantitative data were summarized descriptively, qualitative data were analyzed thematically and comparisons between organizations assessed. Results: Organizational structures, resources, therapists within organizations, assessment tools, and children and families were, on average, viewed as supportive of routine clinical assessment. There were no differences between the Comparison and Commencing organizations except 'therapists within the organization' were viewed as more supportive by the Commencing organizations ( p =  0.037). Five themes were derived from qualitative analyzes: motivation to adopt routine clinical assessment; acquiring and utilizing expertise; ensuring effective ongoing communication; availability and distribution of resources; and therapist perceptions of child and family wishes. Conclusions: Organizations experience challenges to effective and sustained implementation of routine clinical assessment. Adequate resourcing and positive, clear communication were perceived as critical for success. Implications for Rehabilitation: The value of routine clinical assessment of children with cerebral palsy is undisputed. Tailored solutions to organization-specific challenges are required when implementing routine clinical assessment for children with cerebral palsy. Positive, clear communication of organizational priorities by management may assist AHPs to prioritize workload activities when changing practice.